Live animal and meat export value chains for selected areas in Ethiopia: constraints and opportunities for enhancing meat exports - Legese, G.; Teklewold, H.; Alemu, D.; Negassa, A. (International Livestock Research Institute, 2008)
The Ethiopian live animal and meat export marketing system is operating in an environment characterized by several constraints that needs the attention and action of the government and other non-governmental development organizations. Despite the reported high livestock population of the country, the major meat and live animal exporters are complaining of shortage of supply and inferior quality of animals (especially shoats). The problem could be because of the constraints in the marketing system of exporters themselves, the market information system, poor market infrastructures like road, seasonality in production, competition of the domestic and the export sector, problems in the production system, or a combination of several factors. Thus, it is imperative to identify the major factors contributing to the reported supply shortage that has hindered smooth functioning of the Ethiopian live animal and meat export market and take appropriate action as much as possible. This study, therefore, characterizes live animal and meat export value chains to determine constraints and opportunities for enhancing the efficiency of meat export from Ethiopia. The study was conducted using a Rapid Market Appraisal (RMA), which is a method that offers a quick and effective means for: learning about the main characteristics of the marketing system; mapping the supply chains, understanding constraints and opportunities, and generating information as a basis for designing follow-up research such as focused survey of value chain components and actors.